Kriminalisasi Penggunaan Deepfake dalam Tindak Pidana Penipuan dan Pencemaran Nama Baik: Tantangan dan Solusi Hukum - Putri, Silvia Maharani Iskandar; Salsabila, Nashwa; Hosnah, Asmak UI (Universitas Muhammadiyah Kotabumi, 2024)
The increasing use of deepfake technology is causing new dangers in digital crimes like fraud and defamation. This technology can change audio-visual content in a way that makes it hard to tell apart from the original recording. This can allow criminals to use deepfakes for fraud or to harm someone's reputation without them or the public knowing. This journal analyzes how deepfakes are used for fraud and defamation in Indonesia. It looks for legal solutions to address these issues. This study used a normative legal research method to discover that the Electronic Information and Transaction Law (UU ITE) can catch criminals using deepfakes. However, there is a legal gap that makes it difficult to enforce the law effectively. The main problems with making deepfake use illegal are the absence of clear rules and limited knowledge of the technology among law enforcement officers. To fix these problems, it is suggested to update rules about deepfakes and provide more training for law enforcement. Law enforcement can improve their ability to fight crimes involving deepfake technology by taking the right actions. This will help keep the public safe from the harmful effects of deepfake technology.